Evidence of Linezolid Resistance and Virulence Factors in Enterococcus spp. Isolates from Wild and Domestic Ruminants, Italy - Camilla Smoglica; Alberto Vergara; Simone Angelucci; Anna Rita Festino; Antonio Antonucci; Fulvio Marsilio; Cristina Esmeralda Di Francesco (MDPI AG, 2022)
The aim of this study was to evaluate the resistance patterns against selected critically and highly important antibiotics (quinupristin/dalfopristin, vancomycin, and linezolid) in 48 Enterococcus isolates obtained from wild (red deer and Apennine chamois) and domestic (cattle, sheep, and goats) ruminants living with varying degrees of sympatry in the protected area of Maiella National Park (central Italy). According to CLSI breakpoints, 9 out of 48 isolates (18.8%) showed resistance to at least one antibiotic. One Apennine chamois isolate was resistant to all tested antibiotics. The PCR screening of related resistance genes highlighted the occurrence of msrC or cfrD in seven Enterococcus resistant isolates. In addition, msrC and vanC genes were amplified in susceptible isolates. Specific sequences of virulence genes (gelE, ace, efa, asa1, and esp) related to pathogenic enterococci in humans were amplified in 21/48 isolates (43.75%), belonging mostly to wild animals (15/21; 71.42%). This is the first report of linezolid-resistant enterococci harboring virulence genes in Italian wildlife with special regard to the red deer and Apennine chamois species. The results allow us to evaluate the potential role of wild animals as indicators of antibiotic resistance in environments with different levels of anthropic pressure.